Impact of self-heating and substrate effects on small-signal output conductance in UTBB SOI MOSFETs - Makovejev, Sergej; Raskin, Jean Pierre; Mohd Khairuddin, Md Arshad, Dr.; Flandre, Denis; Olsen, Sarah H.; Andrieu, François; Kilchytska, Valeria I. (Elsevier Ltd, 2013)
Link to publisher's homepage at http://www.elsevier.com/